2021
DOI: 10.1017/s1368980021002810
|View full text |Cite
|
Sign up to set email alerts
|

Higher-diet quality is associated with higher diet costs when eating at home and away from home: National Health and Nutrition Examination Survey, 2005–2016

Abstract: Objectives: To evaluate the association between diet quality and cost for foods purchased for consumption at home and away from home. Design: Cross-sectional analysis. Multivariable linear regression models evaluated the association between diet quality and cost for all food, food at home, and food away from home. Setting: Daily food intake data from the National Health and Nutrition Examination Survey (2005-2016). Food prices were derived using data from multiple, publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
(66 reference statements)
1
20
0
Order By: Relevance
“…Food loss and waste (retail loss, inedible portions, and consumer waste) can be estimated through a three-step procedure that links the LAFA data series, the FCID, and the NHANES [28,32]. The first step requires applying simple algebra to the food loss/waste rates and the available data in the LAFA data series to disaggregate inedible portions from cooking loss and uneaten food, which are otherwise aggregated under the heading "loss at the consumer level" (these calculations are described in detail elsewhere [77]). Data are not available in the LAFA data series to disaggregate cooking loss from uneaten food; therefore, it can be assumed that these collectively represent consumer food waste.…”
Section: Data Integration: Food Loss and Wastementioning
confidence: 99%
“…Food loss and waste (retail loss, inedible portions, and consumer waste) can be estimated through a three-step procedure that links the LAFA data series, the FCID, and the NHANES [28,32]. The first step requires applying simple algebra to the food loss/waste rates and the available data in the LAFA data series to disaggregate inedible portions from cooking loss and uneaten food, which are otherwise aggregated under the heading "loss at the consumer level" (these calculations are described in detail elsewhere [77]). Data are not available in the LAFA data series to disaggregate cooking loss from uneaten food; therefore, it can be assumed that these collectively represent consumer food waste.…”
Section: Data Integration: Food Loss and Wastementioning
confidence: 99%
“…By contrast, FCID is the only food composition database that disaggregates NHANES mixed dishes into ingredients that map onto agricultural commodities, which can then be linked with data on food waste from the Loss-adjusted Food Availability data series ( 38 ), as described elsewhere ( 9 ). These linked FCID-LAFA data can be used to evaluate the association between food waste and multiple indicators of sustainability, including agricultural resource use ( 26 , 27 ), environmental impacts ( 25 ), diet quality ( 26 , 27 ), and consumer food expenditures ( 28 , 29 ). The present study allows these linkages to be extended to more contemporary data on food intake from NHANES 2011–2018, thereby filling an important data gap.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, researchers only used NHANES data up until 2010 to align with the year FCID was last updated ( 21 , 25 , 40 ), which does not reflect changes in food consumption that have occurred since that time. Others have combined FCID 2001–2010 with NHANES data up to 2016 with ( 28 , 29 ) and without ( 26 ) imputation to fill data gaps, and demonstrated that incomplete linkages led to a reduction of daily Total Food Demand (sum of retail loss and consumer purchase amount) by 10% ( 26 ) and a reduction of daily consumer food expenditures by 7 ( 28 ) to 15% ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AHEI-2010 is a diet quality index based on foods or food components associated with chronic disease risk [ 17 ]. In this study, AHEI-2010 is composed of nine components: fruit, vegetables, whole grains, omega-3, nuts and legumes, polyunsaturated fatty acids, sugar-sweetened beverages, red and processed meat, and sodium.…”
Section: Methodsmentioning
confidence: 99%